Dissemination strategy for Lean thinking in health care. Issue 5 (2014) - Petra Dannapfel; Bozena Poksinska; Kristin Thomas
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to contribute to knowledge about dissemination strategies for Lean thinking throughout multiple healthcare organisations. Design/methodology/approach – The Östergötland county council, Sweden (CCÖ) was chosen as a case study for an healthcare Lean‐thinking dissemination strategies. Document analysis and interviews were used and results were compared with similar strategies employed by staff at the National Health Service Institute for Innovation (NHSI) and improvement in Great Britain and the Odense University Hospital in Denmark. Findings – The Lean improvement programme was introduced to tackle challenges such as an ageing society, rising care expectations and budgetary and economic constraints. It was designed as a long‐term programme to create added value for patients and employee involvement. The dissemination strategy was: forming clear visions and objectives; piloting; training potential adopters; and formal dissemination. The CCÖ strategy was focused primarily on managers and was not meant to involve all staff until the implementation stage. Staff at the NHSI attempted to address nurses' needs during dissemination, which questioned whether the CCÖ managers' dissemination strategy is sustainable. Practical implications – This paper inspires healthcare managers and decision makers who aim to disseminate Lean production in their organisations. Originality/value – There are many case studies describing Lean implementation in single healthcare organisations, but little is known about effective dissemination and implementation strategies in large healthcare systems. The authors, therefore, suggest activities for developing and implementing dissemination strategies in multiple healthcare organisations. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors thank the Östergötland county council staff for taking part and providing information. </ack>